Silicone implants with smooth surfaces induce thinner but denser fibrotic capsules compared to those with textured surfaces in a rodent model - Fischer, Sebastian; Hirche, Christoph; Reichenberger, Matthias; Kiefer, Jurij; Diehm, Yannick; Kneser, Ulrich (PLOS ONE, 2015)
Purpose Capsular contracture is the most frequent long-term complication after implant-based breast reconstruction or augmentation. The aim of this study was to evaluate the impact of implant surface properties on fibrotic capsule formation in an animal model. Materials and Methods Twenty-four rats received 1 scaled down silicone implant each; 12 of the rats received implants with textured surfaces, and the other 12 received implants with smooth surfaces. After 60 and 120 days, rats in each group underwent 7-Tesla Magnetic Resonance Imaging (MRI) and high-resolution ultrasound (HR-US), and specimens of the capsules were acquired and used to measure capsule thickness through histology, collagen density through picro sirius red staining, and analyses of expression of pro-fibrotic and inflammatory genes (Collagen1-4, TGFb1, TGFb3, Smad3, IL4, IL10, IL13, CD68) through qRT-PCR. Furthermore, MRI data were processed to obtain capsule volume and implant surface area. Results On day 60, histology and HR-US showed that fibrotic capsules were significantly thicker in the textured implant group with respect to the smooth implant group (p<0.05). However, this difference did not persist on day 120 (p=0.56). Capsule thickness decreased significantly over the study period in both smooth and textured implant groups (p<0.05). Thickness measurements were substantiated by MRI analysis and volumes changed accordingly. Implant surface area did not vary between study dates, but it was different between implant types. On day 60, the density of collagen in the fibrotic capsules was significantly lower in the textured implant group with respect to the smooth group (p<0.05), but again this difference did not persist on day 120 (p=0.67). Collagen 1 and CD68 were respectively over- and under expressed in the textured implant group on day 60. Significant differences in the expression of other genes were not observed. Conclusion Silicone implants with textured surfaces led to temporarily thicker but less dense fibrotic capsules compared with smooth surfaces. 7-Tesla MRI and HR-US are capable for non-invasive in-vivo assessment of capsular fibrosis in an animal model and can provide unique insights into the fibrotic process by 3D reconstruction and surface area measurement.